Influence of International Standards of Internal Auditing on the Proficiency of Internal Audit Mechanism in Public Sector Universities of Pakistan - Qadeer, Zahid; Abbas, Sammar; Ahmed, Tanveer (Audit and Accounting Review, 2024)
The current study aims to explore how the International Standards of Internal Auditing (ISIA) impact the proficiency of Internal Audit (IA) mechanism in the public sector of Pakistan. The study targets the public sector Higher Education Institutes (HEIs) of Pakistan which are the recipients of hefty financial resources from government. A questionnaire was distributed to 250 employees working in Internal Audit and Finance Department besides the members of statutory bodies of public sector HEIs of all five provinces (stratum) across Pakistan by using the purposive sampling. One hundred and fifty (150) valid responses were received back. The Institute of Internal Auditors (IIA) has framed two broader categories of ISIA, for instance (i) Attribute Standards (IAS) (ii) Performance Standards (IPS.) By deploying SPSS version 22.0, the results of regression analysis amongst ISIA and IA mechanism reveals that in the category of attribute standards of internal auditing, 3 out of 4 standards have a significant positive impact on the proficiency of (IA) mechanism in public sector HEIs of Pakistan. While, in the category of performance standards of internal auditing; only 3 out of 6 standards have a significant positive impact on the proficiency of (IA) mechanism. The findings would be useful in strengthening the Internal Audit Functions (IAFs) in public sector of Pakistan. Policymakers are recommended to implement the international standards of internal auditing which may lead towards enhanced proficiency of IA mechanism in public sector.